Loyal to god: Old Believers, oaths and orders. Issue 4 (8th August 2017) - Martin, Dominic A.
ABSTRACT: Since the reign of Peter the Great, the Russian sovereign, be it Tsar, Soviet or Putin, has required demonstrations of 'loyalty' that evidence subjects' interior as well as exterior states. This article explores, through historical and current ethnographic examples, how Old Believers, a dissenting movement of Russian Orthodox Christians, have sought to reconcile this worldly demand with their overarching allegiance to the Kingdom of God, and their refusal to acknowledge a separation between the spiritual and the temporal. This dichotomy is particularly problematized around the swearing of oaths of fealty and the giving and receiving of decorations and orders that vouchsafe loyalty to state or sovereign.